Irgendwo in Berlin . Somewhere in Berlin - Lamprecht, Gerhard (Germany, 1946)
The inhabitants of shattered post-war Berlin are portrayed with psychological precision by veteran director Gerhard Lamprecht, who also directed Emil and the Detectives